Analysis of the level of concentration and meditation, in the production process in the tasks carried out through the telework modality - Rojas, Karin (2020)
ABSTRACT In these moments of confinement, many of the different activities that are carried out in person, are now being prepared in a virtual way. Work is one of the activities that have most adapted to this new way of working, therefore many of the activities that cannot be carried out in person, are developed in the form of teleworking. This new reality has made our house become the office, and with it new ways of distracting us arise, such as having to do chores at home, our children who are also in online class, the tasks of the house, among other activities of the house. In the present work, the levels of attention and meditation in the moments that the person is teleworking are evaluated by means of a computer brain device, the results indicate that people are very distracted at home as a result of the distracting agents; there is a greater degree of concentration when these distracting agents are removed.